Nominee Contract Practice on Ownership of Foreign National Land in Indonesia - Reni Anggriani; Ayura Monica Zandra (Jurnal Hukum Novelty, 2021)
Introduction: The nominee agreement in practice is done as legal smuggling against land control for foreigners based in Indonesia, which the Agrarian Principal Law limits. Such restrictions result in foreigners finding a way to obtain property rights under the Nominee Agreement and b the basis of Article 21 paragraph (1) of the fundamental agrarian law of land ownership by foreign nationals with proprietary status contrary to the principle of nationality.Purpose/Objective Study: This research aims to find out how the practice of nominee agreements in land ownership for foreign nationals in Indonesia and the legal consequences of nominee agreements in the application of transfer of property rights to land in Indonesia.Design/Methodology/Approach: This study is normative juridical research beginning on a legal event and then looking for references to a norm system. This legal research is conducted by examining primary and secondary legal materials and non-legal materials relating to nominee contract practice on ownership of foreign national land in Indonesia. In this study, the approach was the statute approach by examining all laws and regulations relating to legal issues and case approach by examining several cases that have a relationship with the legal issues to be discussed.Findings: The result of this study is that the nominee agreement made to transfer ownership of property rights to Foreign Nationals contrary to Article 26 paragraph (2) of the Agrarian Principal Law, based on Article 1320 of the Civil Code, does not meet the objective requirement that lawful clause. The agreement becomes null and void and has no binding power and cannot be used for the basis of rights in obtaining ownership of land for Foreign Nationals in Indonesia.Paper Type: Research article